The RBCC Gene RFP2 (Leu5) Encodes a Novel Transmembrane E3 Ubiquitin Ligase Involved in ERAD - Lerner, Mikael (The American Society for Cell Biology, 2007)
RFP2, a gene frequently lost in various malignancies, encodes a protein with RING finger, B-box, and coiled-coil domains that belongs to the RBCC/TRIM family of proteins. Here we demonstrate that Rfp2 is an unstable protein with auto-polyubiquitination activity in vivo and in vitro, implying that Rfp2 acts as a RING E3 ubiquitin ligase. Consequently, Rfp2 ubiquitin ligase activity is dependent on an intact RING domain, as RING deficient mutants fail to drive polyubiquitination in vitro and are stabilized in vivo. Immunopurification and tandem mass spectrometry enabled the identification of several putative Rfp2 interacting proteins localized to the endoplasmic reticulum (ER), including valosin-containing protein (VCP), a protein indispensable for ER-associated degradation (ERAD). Importantly, we also show that Rfp2 regulates the degradation of the known ER proteolytic substrate CD3-δ, but not the N-end rule substrate Ub-R-YFP (yellow fluorescent protein), establishing Rfp2 as a novel E3 ligase involved in ERAD. Finally, we show that Rfp2 contains a C-terminal transmembrane domain indispensable for its localization to the ER and that Rfp2 colocalizes with several ER-resident proteins as analyzed by high-resolution immunostaining. In summary, these data are all consistent with a function for Rfp2 as an ERAD E3 ubiquitin ligase.